Optimalisasi Keterampilan Menulis Melalui Sistem Pembelajaran Berbantuan Deep Learning - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
Writing skills are a complex language competency because they require critical thinking skills, mastery of language structures, and creativity in expressing ideas. However, writing learning still faces challenges, especially in providing fast, personalized, and appropriate feedback to students' needs. Along with the development of artificial intelligence technology, especially deep learning, new opportunities have emerged to optimize the writing learning process. This literature review article aims to analyze the role of deep learning-assisted learning systems in improving students' writing skills. The method used is a literature study by reviewing various recent studies related to the implementation of deep learning in the context of language education, especially writing. The results of the study indicate that deep learning can contribute in five main aspects, namely: (1) automation of text analysis to detect grammatical errors and writing style, (2) personalization of learning through content recommendations that suit students' needs, (3) increasing creativity by providing stimulus ideas through artificial intelligence-based systems, (4) efficiency of the evaluation process through automatic and fast feedback, and (5) integration of collaborative learning based on digital platforms that enable students to learn to write interactively. Thus, the application of deep learning in writing learning can be an innovative strategy to improve the effectiveness and quality of language learning in the digital era. Further research is needed to develop adaptive, ethical learning models that are oriented toward strengthening students' digital literacy.